Trajectory of 75 years of Indian Agriculture after Independence - Ghosh, P. K.; Das, Anup.; Saxena, Raka.; Banerjee, Kaushik; Kar, Gouranga; Vijay, D. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This edited book focus on highlighting the evolution of Indian agriculture over the past 75 years of independence, covering every sector, viz. crop science, horticulture, management of biotic & abiotic stress, post-harvest quality management, livestock, fisheries, mechanization, marketing and human resource development. The book has 30 chapters from most experienced researchers and academicians who are actively engaged in research work on the subject area of the book. The book is in line with the strategy for new India @ 75' brought out by NITI Ayog. It highlights India's success stories in innovation, technology, enterprise and efficient management together to achieve overall growth while making available food, required nutrition and others ecological services. It also asses the India's preparedness in terms of commitment toward sustainable development goal SDG). The book is a relevant reading material for both students and researchers and policy makers.
Chapter 1. Indian agriculture @75: Unraveling the trend and Trajectory -- Chapter 2. Contribution towards food supply and security -- Chapter 3. Changing Structure of Rural Employment and its Implications for Agriculture in India -- Chapter 4. Contributions of Technologies to Agricultural Development in India -- Chapter 5. Evolution of The Indian Seed Sector and its Role in Agricultural Growth -- Chapter 6. Rice research in India: A historical perspective -- Chapter 7. Wheat -- Chapter 8. Maize and Millets -- Chapter 9. Pulses -- Chapter 10. Role of Oilseeds and Oil Palm in Food, Nutritional and Income Security -- Chapter 11. Indian Horticulture @75 years of Independence -- Chapter 12. Growth and Developments in Livestock Sector -- Chapter 13. Fishery -- Chapter 14. Status of commercial crops (Jute, Cotton and Sugarcane) -- Chapter 15. Natural Resource Management to attain Food and Environment Security -- Chapter 16. Water -- Chapter 17. Land - a vital component of natural resource: Pre- and post-Independence status, challenges and options to achieve food and environmental security in India -- Chapter 18. Farm Mechanization -- Chapter 19. Forests to attain Food and environment security -- Chapter 20. Agrometeorological Research in India Towards Food and Environment Security -- Chapter 21. Sustainable Production Systems in Indian Agriculture -- Chapter 22. Dryland Agriculture -- Chapter 23. Biotic stress management in India- an endless fight since pre-independence -- Chapter 24. Invasive and Transboundary Pests -- Chapter 25. Bio pesticides -- Chapter 26. Trajectory of Market Reforms in India Facts and Foundation -- Chapter 27. Prospects of Agribusiness and Entrepreneurship -- Chapter 28. The Food Processing Industry in Post-Independence Era: Performance and Way Forward -- Chapter 29. Transformation of Agricultural Extension System in India -- Chapter 30. Recent policy reforms in India.
Keywords: Agriculture; Agronomy; Subsistence farming; Agricultural biotechnology; Agriculture; Agronomy; Subsistence Agriculture; Agricultural Biotechnology